Genotoxicity of the medicinal plant Maytenus robusta in mammalian cells in vivo. - Raymundo, T. M. [UNESP]; Favilla, M. [UNESP]; Niero, R.; Andrade, S. F.; Maistro, E. L. [UNESP] (Genetics and Molecular Research, 2012)
Plants belonging to the Celastraceae family have been used in traditional medicine for their analgesic, anti-inflammatory and anti-ulcerogenic properties, among others. Maytenus ilicifolia is the principal species of this family, and is used in the treatment of gastric ulcers. However, owing to its inadequate management in Brazil, the species is becoming extinct and is being substituted with Maytenus robusta, which also displays gastroprotective activity. The aim of this study was to evaluate the genotoxic effects of M. robusta hydroalcoholic extract in vivo, using the comet assay and micronucleus test. Three doses (50, 250 and 500 mg/kg body weight) were administered to mice orally 2 times at 24-h intervals. Cytotoxicity was assessed by scoring 200 consecutive total polychromatic and normochromatic erythrocytes to calculate their ratio. Parametric (analysis of variance/Tukey) and non-parametric (Kruskal-Wallis/Dunn post hoc) tests were used to evaluate the results according to the nature of the data distribution. The results showed a significant increase in the frequency of DNA damage on leukocytes at the 2 higher doses tested, but the extract did not enhance micronucleus frequency in bone marrow cells. Our findings showed that after 48 h of treatment, M. robusta hydroalcoholic extract had weak genotoxic effects but no clastogenic effects in mice cells.
Keywords: DNA; mutagenic agent; plant extract; animal; bone marrow cell; chemistry; comet assay; drug effect; erythrocyte; leukocyte; male; mammal; Maytenus; medicinal plant; metabolism; micronucleus; mouse; mutagen testing; Animals; Bone Marrow Cells; Comet Assay; Erythrocytes; Leukocytes; Male; Mammals; Mice; Micronuclei, Chromosome-Defective; Mutagenicity Tests; Mutagens; Plant Extracts; Plants, Medicinal